2018
DOI: 10.22215/timreview/1145
|View full text |Cite
|
Sign up to set email alerts
|

To Internationalize or Not to Internationalize? A Descriptive Study of a Brazilian Startup

Abstract: IntroductionTechnology-based startups have been growing exponentially in Brazil (ABStartups, 2018). Faced with a limited market with global potential, a technology startup aims to internationalize early and fast. These high-tech companies provide innovative products and services and operate as pioneers in a small global niche market (Neubert, 2015).A company born of a small, open economy is often forced to internationalize early and fast to become profitable (Neubert, 2016a). However, early and rapid internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The review of related literature revealed that there are two broad branches for researching the hydrogen economy. One is related to the investigation of the present status of the hydrogen economy and its roadmaps, and it recommends some policies to boost the growth of the hydrogen economy [2,4,5,9,10,18,20,27,29,30].…”
Section: Limitations Of the Research On The Hydrogen Economy And Significance Of A Systematic Framework For Implementing The Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The review of related literature revealed that there are two broad branches for researching the hydrogen economy. One is related to the investigation of the present status of the hydrogen economy and its roadmaps, and it recommends some policies to boost the growth of the hydrogen economy [2,4,5,9,10,18,20,27,29,30].…”
Section: Limitations Of the Research On The Hydrogen Economy And Significance Of A Systematic Framework For Implementing The Strategymentioning
confidence: 99%
“…These initiatives can also be the basis for the long-term innovation and economic development that correspond to environmental constraints. Thus, the initiatives reduce the gap between the regional inequalities within a country or those between countries [20][21][22]. As aforementioned, the Korean Green New Deal that was announced on 14 July 2020, as well as the "Hydrogen Economy Roadmap" (January 2019), have announced the dual goals of considerably enhancing the hydrogen economy, and alleviating the resultant regional inequality within the country [8,23].…”
Section: Introductionmentioning
confidence: 99%
“…Internationalisation is understood as the company's bridge to the markets outside the natural geographical environment. An internationalised company presents lower financial risk, is less vulnerable to internal market crises, and generally has higher levels of profitability, which makes it more competitive [39][40][41][42]. In addition, internationalisation multiplies commercial and financial flows, has a positive effect on other economic activities and promotes the exchange of knowledge and good practices between the different regions and/or countries involved [6,43].…”
Section: Internationalisation In Hospitality and Tourismmentioning
confidence: 99%
“…The success of an internationalisation process is conditioned by a series of environmental factors, and by several attributes (that is, the capabilities, conditions and attitudes) that are within the control of the tourism enterprises [41,[50][51][52], thus depending on a greater extent on business advances in innovation and competitiveness, as well as on business collaboration and networking [53]. This is, internationalisation success depends on those strengths and weaknesses of the business strategy that guarantee the sustainability of the sector.…”
Section: Internationalisation In Hospitality and Tourismmentioning
confidence: 99%
“…Diante de uma economia global cada vez mais tecnológica, o risco ao investir em uma startup é o aprofundamento das diferenças econômicas entre desenvolvido e subdesenvolvido países. Países com poucos recursos correm o risco de sendo ainda marginalizado do desenvolvimento econômico, criado a partir de centros de inovação (SCHERER, 2018).…”
Section: Startupunclassified